Validity and Reliability of the Turkish Version of the Adult Picky Eating Questionnaire - Ayyıldız, Feride; Esin, Kübra (Progress in Nutrition, 2022)
Background and aim: Picky eating (PE) is generally expressed as a behavior seen in childhood, approximately one out of every three adults have been reported to exhibit PE behavior. Also, it is one of the determinant eating behaviors in the diagnosis of eating disorder-Avoidant/Restrictive Food Intake Disorder (ARFID). The aim of the present study was to translate, adapt and validate the Adult Picky Eating Questionnaire (APEQ) into Turkish.Methods: This study included 1135 adults (556 male, 579 female) with a mean age of 30.54 ± 11.73 (ranged from 18 to 63 years old). The APEQ was translated and adapted to Turkish according to the Beaton guideline. Eating Attitudes Test-Short Form (EAT-26) was used in the evaluation of eating behavior, and Kessler Psychological Distress Scale was used for psychological evaluation.Results: Items 2 and 3 were removed from the scale because total item correlation of these items was below 0.30. The Cronbach's alpha for the total scale of the APEQ-Tr was 0.731, with 0.630, 0.602, 0.627, and 0.671 for Meal presentation, Food variety, Meal disengagement and Taste aversion, respectively. APEQ-Tr, which is related to eating disturbance and psychological distress, showed an acceptable reliability with all its subscales.Conclusions: In conclusion, the Turkish version of APEQ (APEQ-Tr) can be used to evaluate PE in the Turkish population.